2023
DOI: 10.1021/acs.jmedchem.3c00465
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Dual-Target Estrogen Receptor α Degraders with Tubulin Inhibitory Activity for the Treatment of Endocrine-Resistant Breast Cancer

Abstract: Endocrine resistance remains a significant problem in the clinical treatment of estrogen receptor α-positive (ERα + ) breast cancer (BC). In this study, we developed a series of novel dual-functional ERα degraders based on a bridged bicyclic scaffold with selenocyano (SeCN) side chains. These compounds displayed potent ERα degradation and tubulin depolymerization activity. Among them, compounds 35s and 35t exhibited the most promising antiproliferative and ERα degradation activity in multiple ERα + BC cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For instances, p ‐XSC ( I ) was detected to display activity in inhibiting the viability of prostate cancer cells [4b] . Selenocyanate derivative II was reported to exhibit the promising antiproliferative activity in treating breast cancer, [7] while selenocyanatoisoxazole III and diselane IV were proved to be potent antileishmanial agents [8] . Especially, 3‐ selenocyanate substituted indole ( V ) was found to be an antifungal agent for the treatment of superficial and mucocutaneous infections (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…For instances, p ‐XSC ( I ) was detected to display activity in inhibiting the viability of prostate cancer cells [4b] . Selenocyanate derivative II was reported to exhibit the promising antiproliferative activity in treating breast cancer, [7] while selenocyanatoisoxazole III and diselane IV were proved to be potent antileishmanial agents [8] . Especially, 3‐ selenocyanate substituted indole ( V ) was found to be an antifungal agent for the treatment of superficial and mucocutaneous infections (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the decline in estrogen biosynthesis could counteract SERMs’ agonistic effects on tissues like the uterus . Certain dual-targeting inhibitors ( 6 – 8 ) have been identified for the prevention of estrogen production or the inhibition of ER signal transduction in BC. Although ERα/ARO dual-targeting drugs have not yet entered clinical trials, these studies have demonstrated the fundamental structural characteristics of ERα/ARO dual-targeting candidates, revealing that multitarget compounds may be feasible therapies for treating estrogen receptor-positive (ER + ) BC. Conversely, Ful stands as the initial FDA-approved SERD to exhibit clinical advantages in the management of patients dealing with advanced or metastatic ERα + BC.…”
Section: Introductionmentioning
confidence: 99%
“…Ribociclib and Palbociclib (Figure 3), two typical selective CDK4/6 inhibitors, have been used for the clinical treatment of estrogen receptorpositive (ER + ) advanced breast cancer. [18] These drugs can directly occupy the kinase ATP-binding site, and lead to the loss of catalytic activity of the cyclin D-CDK4/6 complex in a competitive manner, triggering G 1 phase arrest in tumor cells. However, owing to clinical limitations such as low efficacy, narrow anti-tumor spectrum and acquired drug resistance when used as mono-therapy, [19] they can only be used in combination.…”
Section: Introdoctionmentioning
confidence: 99%